2015
DOI: 10.1021/acs.jpcc.5b05514
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Conformations of Alkanedithiols on Gold and Silver Nanoparticles in Water

Abstract: Organodithiols with two distal thiols have been used extensively in gold and silver nanoparticle (AuNP and AgNP) applications. However, understanding the structures and conformations of organodithiols on these nanoparticles is challenging. Reported in this work is a combined surface enhanced Raman spectroscopy (SERS), transmission electron microscope (TEM), inductively-coupled plasma mass-spectrometry (ICP-MS), and localized surface plasmonic resonance (LSPR) study of alkyldithiol (ADT, (HS-(CH 2 ) n -SH, n= 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
(112 reference statements)
1
10
0
2
Order By: Relevance
“…20 Gold NPs wrapped by polymer chains cannot be eliminated from GNP-15 directly because of their exceptional chemical stability. As far as we know, similar interaction between gold NPs and thiolate molecules has been reported for silver NPs, 32 and novel NC hydrogels can be prepared by replacing gold NPs with silver NPs through a photochemical reaction, providing GNP hydrogels with a similar polymer network. To obtain a uniform network without the introduction of gold NPs, we found that silver NPs wrapped in the network could be eliminated by ammonium persulfate, producing a uniform structure but with larger pores ( Figures S9A and S9B), and the same gel network as GNP-15 was obtained and defined as GNP-0 (etching).…”
Section: Mechanical Performance Of Gnp Hydrogelsmentioning
confidence: 57%
“…20 Gold NPs wrapped by polymer chains cannot be eliminated from GNP-15 directly because of their exceptional chemical stability. As far as we know, similar interaction between gold NPs and thiolate molecules has been reported for silver NPs, 32 and novel NC hydrogels can be prepared by replacing gold NPs with silver NPs through a photochemical reaction, providing GNP hydrogels with a similar polymer network. To obtain a uniform network without the introduction of gold NPs, we found that silver NPs wrapped in the network could be eliminated by ammonium persulfate, producing a uniform structure but with larger pores ( Figures S9A and S9B), and the same gel network as GNP-15 was obtained and defined as GNP-0 (etching).…”
Section: Mechanical Performance Of Gnp Hydrogelsmentioning
confidence: 57%
“…Besides the pH measurement data, another critical supporting evidence that organothiol binds to AuNPs through deprotonation pathway is the comparison of the SERS spectra of BuT and DBDS (Figure ). The S–H stretching Raman peak (∼2600 cm –1 ) in neat BuT (Figure a) is absent in BuT in 1 M NaOH (Figure b), suggesting that BuT is in thiolate form in 1 M NaOH. BuT adsorption onto AuNP is evident from the absence of the S–H stretching Raman peak (∼2600 cm –1 ) in the BuT SERS spectra (Figure c), while DBDS adsorption onto AuNP is experimentally confirmed by the disappearance of disulfide (S–S) stretching Raman feature in the ∼500 cm –1 region (Figure e) compared to neat DBDS in Figure f. , These results indicate that the S–H peak in BuT and the S–S peak in DBDS are both cleaved upon their binding to AuNPs (Figure c,e). However, the SERS spectrum of the BuT in water is much more similar to the SERS spectrum of BuT dissolved in 1 M NaOH (Figure c,d), but different from the SERS spectrum of DBDS adsorbed onto AuNP in water (Figure e), particularly for the spectral feature from 1000 to 1500 cm –1 region.…”
Section: Resultsmentioning
confidence: 96%
“…Covalent interactions are often restricted to analytes that present a functional moiety such as thiol or amine functionalities. [15][16] On the other hand, electrostatic interactions are restricted to charged analytes interacting with an opposite charged plasmonic substrate. [17] Unfortunately, most analytes do not present such affinity towards the plasmonic substrate.…”
Section: Introductionmentioning
confidence: 99%